Contractor Management Model to Improve Safety and Productivity Conditions in an Industrial Company - Rojas Albán, Franco (2022)
Outsourcing contributes to business development. On some occasions, in order to secure low-cost bids, contractors agree to work under unsafe conditions; on other occasions, the client exerts pressure so that the service is completed ahead of schedule, causing contractors to take “shortcuts” and evade safety controls, which increases the risk of serious injury, chronic illness or even death. In Peru, there is no contractor management model in place to improve safety conditions and promote third-party productivity. Via statistical tests and correlation of variables, this research has developed and implemented a management model that describes the minimum requirements that must be met to avoid incidents and improve contractor productivity. It includes regulations from recognized national and international agencies and encompasses the best work practices acquired in more than 30 years of experience in the management of incidents in manufacturing, construction, steelmaking and mining.